The relative age effect: coaches' choices as evidence of social influence on youth handball - Krahenbühl, T.; Leonardo, L. (Journal of Physical Education and Sport, 2020)
The Relative Age Effect (REA) is the object of study in the sports environment with results that relate this effect to the maintenance or withdrawal of athletes in sports practice. However, this effect is seen from a biological perspective and little is observed about the social effects resulting from the initial advantages that may be precursors of future benefits. Purpose: The aim of this study was to verify the participation time, the coach's perception about the athletes' performance, the game position and their relationship with the age of under-14 female and male handball players in a state competition in Brazil. Methods: Where participated in this study 88 under-14 handball athletes from four women's teams and four men's teams and eight coaches from these respective teams, in a total of 16 matches analyzed. For this, it were collected the birthdates, average time played and the offensive positions that each athlete participated in the matches. Also, each coach ranked their team`s players based on himself subjective perceived performance. Players were divided by gender, and each gender was divided into four quartiles by age, with Q4 being the youngest and Q1 the oldest. Results: Older athletes play more time than younger athletes, coaches perceive older players as better players, older players in the position of point guard and younger players performs more in extreme positions. Conclusion: It was verified that the coach's perception about the athletes' performance is directly related to the player time participation and the player's position in the game. Thus, the RAE is determined by the people involved in the sport context, in this case, the coach and his perception about the athletes' development, which influences the opportunities for the practice, potentiating social phenomena such as Pygmalion and Galatea effects.